Determinants of Digital Payment Adoption among University Students in Higher Education Institutions - Aulia Az-Zahra; Zulfikar Zulfikar (Jurnal Economic Resource, 2026)
The rapid growth of digital payment systems has transformed financial behavior among university students. The purpose of this study is to examine the effects of online shopping trends, self-control, financial literacy, impulsive buying, and saving awareness on the use of digital payments among students at the FEB UMS. This research employed a quantitative method using a structured questionnaire distributed to 117 respondents. Multiple linear regression was used with SPSS to evaluate the data. The outcomes indicate that online shopping trends, financial literacy, impulsive buying, and saving awareness significantly influence digital payment usage, while self-control shows a negative but insignificant effect. Simultaneously, all variables significantly affect the use of digital payments. These findings highlight the importance of behavioral and financial factors in shaping students’ adoption of digital payments.